Safeguards Assessments : Review of Experience. (Policy Papers; Policy Paper ;, 2015)
This paper reviews experience with the safeguards assessment policy since the last review in 2010. The policy is subject to periodic reviews by the Executive Board. The policy's main objective is to mitigate risks of misuse of Fund resources and misreporting of monetary data under Fund arrangements. Consistent with past reviews, an external panel of experts provided an independent perspective on the implementation of the policy.